PENGARUH ETIKA KERJA, KEPEMIMPINAN DAN PROFESIONALISME TERHADAP KINERJA KARYAWAN PT LION AIR - Ariyanti, Anik (JURNAL ILMIAH M-PROGRESS, 2018)
This study aims to determine the partial and simultaneous influence of work ethic, leadership and professionalism on employee performance of PT Lion Air. The research hypothesis is that the work ethic, leadership and professionalism partially and simultaneously affect the performance of employees of PT Lion Air. The method used in this research is descriptive verification. The sample in this study was 30 people, which was calculated by Slovin Formula. The result of research mentioned that work ethic, leadership and professionalism partially and simultaneously have a positive and significant effect on employee performance of PT Lion Air. From the value of Adjusted R Square of 0.717, it means that the three independent variables give the influence/contribution of 71.7% to the increase in performance, the remaining 28.3% influenced by other factors. Keywords: Work ethic, leadership, professionalism and employee performance